The UNESCO Conventions for the protection and safeguarding of cultural heritage - López-Hurtado Orjeda, Enrique (2018)
The cultural heritage of each country is characterized by being charged with unrepeatable aspects that denote its unique identity and particular historical trajectory. However, the nature of the threats and the risks faced by assets and patrimonial expressions are quite similar around the world. In this context, the design and implementation of public policies for the protection and safeguarding of cultural heritage face similar challenges at a regional and even global level. The goal of this article is to present the scope of the UNESCO conventions as instruments that  frame  the  issue  of  heritage  from  a  perspective  shared  with  the  signatory  states,  which  seek  to  lay  the foundations for the protection and safeguarding of the cultural heritage through the establishment of commitments and wills shared internationally.